Family Interpersonal Communication Model from an Islamic Perspective: Implications for Conflict, Personality, and Self-Regulated Learning - Hana Musalju Tanwa; A. Rivai Beta (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study examines the model of family interpersonal communication from an Islamic perspective and its implications for family conflict, personality development, and self-regulated learning. The research is grounded in the increasing concern over ineffective family communication patterns that contribute to unresolved conflicts, weak character formation, and low independent learning capacity among adolescents. Therefore, this study aims to develop an integrative communication model that incorporates Islamic values as a framework for understanding family interactions and their educational impact. The study hypothesizes that family interpersonal communication positively influences personality and self-regulated learning, while negatively affecting family conflict. Additionally, personality and family conflict are proposed as mediating variables in the relationship between communication and self-regulated learning. A quantitative approach with an explanatory survey design was employed. Data were collected from Muslim high school students using structured questionnaires and analyzed using Structural Equation Modeling. The results reveal that family interpersonal communication significantly enhances personality development and self-regulated learning, while reducing family conflict. Furthermore, personality and family conflict are found to mediate the relationship between communication and self-regulated learning, indicating that the influence of communication operates both directly and indirectly through psychological and relational processes. These findings confirm that communication grounded in Islamic values such as honesty, empathy, and kindness plays a crucial role in shaping individual behavior and learning autonomy. In conclusion, this study highlights the importance of strengthening family interpersonal communication as a strategic approach to fostering harmonious relationships, positive personality traits, and effective self-regulated learning. The findings contribute to the development of communication and dakwah studies by positioning family communication as a practical domain for the internalization of Islamic values in everyday life.